2015
DOI: 10.3133/sir20155146
|View full text |Cite
|
Sign up to set email alerts
|

Climate and streamflow characteristics for selected streamgages in eastern South Dakota, water years 1945–2013

Abstract: Dakota (Martin and others, 2004). Agricultural activities are extensive throughout eastern South Dakota (fig. 2). The largest cities in the basin have developed along the James, Vermillion, and Big Sioux Rivers, and contribute urban runoff and wastewater effluent discharges to these rivers. About 66 percent of the area in study watersheds in the Big Sioux River Basin is used for cultivated crops (fig. 2C), and other agricultural activities in the basin include livestock and concentrated animal-feeding operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
7
20
1
Order By: Relevance
“…[2015a] observations match recent USGS findings of increased antecedent soil wetness conditions (increasing well levels) in eastern South Dakota [Hoogestraat and Stamm, 2015]. 3.…”
Section: Influence Of Precipitation On Streamflow Changessupporting
confidence: 78%
See 1 more Smart Citation
“…[2015a] observations match recent USGS findings of increased antecedent soil wetness conditions (increasing well levels) in eastern South Dakota [Hoogestraat and Stamm, 2015]. 3.…”
Section: Influence Of Precipitation On Streamflow Changessupporting
confidence: 78%
“…Then, the question is: how did that affect ET from the landscape? For eastern South Dakota, Hoogestraat and Stamm [2015] mention that ''Although some agricultural land . .…”
Section: Effects Of Lulc Change On Base Flowmentioning
confidence: 99%
“…By aggregating Q and P data over seasonal to annual timescales, any significant shifts in the slope and intercept of the Q-P relationship can be assumed to arise from the influence of other drivers, such as LULC or water management. Conversely, if one assumes a constant Q-P relationship at a given location, then the residuals can be used to investigate the factors characterizing the residual streamflow variability [44]. Simple process-based models based on the Budyko hypothesis [45] may also be used to evaluate the effects of aridity (P and evapotranspiration) and other drivers (e.g., effects of crop conversions, irrigation, reservoir storage and urbanization) [46,47]; or to apportion changes in water yield into climate and LULC drivers [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown reduced surface runoff from improved subsurface drainage across the U.S. Midwest [17,19,20], Canada [21,22], Germany [23], and the U.K. [24]. Similarly, recent studies [25][26][27] also reported altered hydrologic responses from agricultural watersheds with artificial subsurface drainage. A study based on eddy covariance tower installed over the fields with and without subsurface drainage in North Dakota (U.S.) reported an increase in ET by 16% and 7% during corn and soybean growing seasons, respectively [28].…”
Section: Introductionmentioning
confidence: 89%